Radiolabeled Heterobivalent Peptidic Ligands: an Approach with High Future Potential for in vivo Imaging and Therapy of Malignant Diseases. Issue 6 (5th April 2013) - Fischer, Gabriel; Schirrmacher, Ralf; Wängler, Björn; Wängler, Carmen
<x xml:space="preserve">Abstract</x> Two‐pronged synergism: We review the recently developed approach of using heterobivalent peptide ligands that interact concomitantly with different receptors on tumor cells. These ligands exhibit highly favorable tumor‐targeting properties and pave the way for the development of drugs for specific, sensitive, and noninvasive tumor imaging and therapy.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>